Research on Local Humidity Environment of Ground Parking Aircraft - Teng Zhang; Sheng Zhang; Yuting He; Xu Du; Binlin Ma (Applied Sciences, 2018)
Local humidity and temperature monitoring of ground parking aircraft were carried out in this study. Changes in the humidity of different bays and the relationship between local humidity and local temperature were investigated. Moreover, the concept as well as a method of calculating the humidity characteristic coefficient (HCC) were put forward, and two models of aircraft local humidity were established using the humidity and temperature of the thermometer shelter as arguments. Furthermore, bays of an airplane were divided into three groups according to differences in local humidity, and the range of the HCC of each group were determined. The results suggest that the rates of change of local humidity and local temperature are negatively correlated, moreover, the theoretical model shows a linear relationship between humidity and temperature, with a negative slope suggesting changes in humidity are inversely proportional to temperature. The ratio of the local environment slope to the external environment slope has a constant value. Finally, bay sealing and temperature features were found to significantly affect local humidity, and average deviations between the monitored humidity and humidity values predicted using the two temperature models were all less than, or equal to, 7.3% relative humidity.